The efficiency asset utilization financial performance and capital structure on manufacturing firm value on the Indonesia stock exchange (IDX) - Eka Kurniasari; Akhmadi Akhmadi; Wawan Ichwanudin (Enrichment : Journal of Management, 2023)
This research was conducted to determine the effect of asset utilization efficiency, financial performance and capital structure on firm value. Specifically to test whether financial performance is able to mediate asset utilization on firm value and test whether capital structure contributes to the relationship between asset utilization - firm value. We conducted research on manufacturing companies listed on the IDX that are listed on the Indonesia Stock Exchange (IDX) in 2019 – 2021. Secondary data obtained from www.idx.co.id. The results of the study show that the efficiency of asset utilization has a significant effect on firm value, financial performance is able to mediate the relationship between asset utilization and firm value. In addition, the relationship between asset utilization and firm value becomes stronger with capital structure. The implication of our research is that good asset utilization efficiency can increase company profits so that it can increase company value, and the company's capital structure can strengthen the effect of asset utilization on company value. The benefit of this research for companies are expected to provide understanding to company management about the role of company growth, asset utilization, capital structure in determining company financial performance and company value.